Respiratory heat loss in Morada Nova sheep in Brazilian semi-arid regions - Oliveira, Steffan Edward Octávio [UNESP]; Costa, Cįntia Carol De Melo [UNESP] (Malque Publishing, 2013)
This study aimed to evaluate the respiratory heat loss in sheep from the equations developed for this species and its relations with meteorological variables in semi-arid regions. The respiratory heat loss (sensible and latent) was estimated through the equations in the literature for four 12-month-old male Morada Nova sheep, kept in an installation with shading of ceramic tiles and a 3-meter-high ceiling. The following environmental variables were measured: air temperature (TA), wind speed (U), relative humidity (RH) and partial vapor pressure (PP{tA}). The physiological variables measured: rectal temperature (TR) and respiratory rate (RR). Statistical analysis was performed based on regression using PROC REG procedure in SAS. The latent respiratory heat loss showed a linear and positive correlation with ambient temperature. However, the respiratory convection showed a linear and negative correlation, but with incipient values. Therefore, the latent heat loss is more important than the sensible one in the respiratory system to maintain thermoregulation of Morada Nova sheep in a semi-arid region of Brazil.
Keywords: Respiratory convection; Respiratory evaporation; Small ruminants; Thermoregulation